Metallogenic models as the key to successful exploration — a review and trends - Walter L. Pohl (Mineral Economics, 2022)
Metallogeny is the science of ore and mineral deposit formation in geological space and time. Metallogeny is interdisciplinary by nature, comprising elements of natural science disciplines such as planetology to solid state physics and chemistry, and volcanology. It is the experimental forefront of research and bold thinking, based on an ever-growing foundation of solid knowledge. Therefore, metallogeny is not a closed system of knowledge but a fast-growing assemblage of structured and unstructured information in perpetual flux. This paper intends to review its current state and trends. The latter may introduce speculation and fuzziness. Metallogeny has existed for over 100~years as a branch of Earth Science. From the discovery of plate tectonics (ca. 1950) to the end of the last century, metallogeny passed through a worldwide phase of formally published 'metallogenetic' maps. In the last decades, a rapidly growing number of scientists, digitization and splendid new tools fundamentally boosted research. More innovations may be expected by the growing use of an evolving systematic 'Geodata Science' for metallogenic research by an increasingly global human talent pool. Future requirements for metallic and mineral raw materials, especially the critical natural elements and compounds that are needed for the nascent carbon-free economy, already drive activities on stock markets and in the resource industry. State geological surveys, academia and private companies embrace the challenges. The new age requires intensified metallogenic backing. In this paper, principles of metallogeny are recalled concerning concepts and terms. A metallogenic classification of ore and mineral deposits is proposed, and the intimate relations of metallogenesis with geodynamics are sketched (ancient lid tectonics and modern plate tectonics). Metallogenic models assemble a great diversity of data that allow an ever better understanding of ore formation, foremost by illuminating the geological source-to-trap migration of ore metals, the petrogenetic and geodynamic–tectonic setting, the spatial architecture of ore deposits and the nature and precise timing of involved processes. Applied metallogeny allows companies to choose strategy and tactics for exploration investment and for planning the work. Based on comprehensive metallogenic knowledge, mineral system analysis (MSA) selects those elements of complex metallogenic models, which are detectable and can guide exploration in order to support applications such as mineral prospectivity mapping, mineral potential evaluation and targeting of detailed investigations. MSA founded on metallogenic models can be applied across whole continents, or at the scale of regional greenfield search, or in brownfields at district to camp scale. By delivering the fundamental keys for MSA, supported by unceasing innovative research, the stream of new metallogenic insights is essential for improving endowment estimates and for successful exploration.
Keywords: 660; Metallogeny; Gold; Lid tectonics; Plate tectonics; Metallogenic models; Metallogeny in exploration; Mineral system analysis